Drone-Based Monitoring Design with IoT System for Surface Temperature and Humidity Measurement - Habiburrahman, H; Mairizwan, M; Sudiar, Nofi Yendri; Yohandri, Y (Department of Physics – Universitas Negeri Padang UNP, 2025)
Vertical temperature and humidity profiles observation has often been studied in meteorology to analyze climate phenomena such as temperature inversion. This observation required a monitoring system that could be operated flexibly, ensured accurate data readings, and was capable of storing the collected data. This research was conducted to design a monitoring system using drone, which offered flexibility in three-dimensional space, and included a cloud-based data logger to store measurement data utilizing the Internet of Things system. The research employed testing methods for the sensors and components used in the system. The results show the system's performance specifications, including the characterization of the DHT22 sensor, testing of the NRF24L01 communication module, data logger, and mechanical system design. The design specifications indicate an average temperature measurement accuracy of 99% and 97.8% for humidity. The temperature reading precision is 1.00, while it is 0.99 for humidity. These results demonstrate that the system functions well.